If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + c) = 2(c + -3) (1 * 3 + c * 3) = 2(c + -3) (3 + 3c) = 2(c + -3) Reorder the terms: 3 + 3c = 2(-3 + c) 3 + 3c = (-3 * 2 + c * 2) 3 + 3c = (-6 + 2c) Solving 3 + 3c = -6 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 3 + 3c + -2c = -6 + 2c + -2c Combine like terms: 3c + -2c = 1c 3 + 1c = -6 + 2c + -2c Combine like terms: 2c + -2c = 0 3 + 1c = -6 + 0 3 + 1c = -6 Add '-3' to each side of the equation. 3 + -3 + 1c = -6 + -3 Combine like terms: 3 + -3 = 0 0 + 1c = -6 + -3 1c = -6 + -3 Combine like terms: -6 + -3 = -9 1c = -9 Divide each side by '1'. c = -9 Simplifying c = -9
| 3w^2-22w=16 | | 10(8c-1)-18=78c+10 | | 19x+(-8)=-44+10x | | 4/a=b/2 | | 5(y-2)=2y-9 | | x^2+(y)x+(y^2-19)=0 | | x^2+xy+y^2=19 | | 4-4x=11+3x | | -6n+5=-5n-11 | | -4y-12=5y+42 | | 8y-2=3y+3 | | 5c+12=7c+10.82 | | (-4a)+3=2a+12 | | -5+12=15x-3-14x | | 7y-12y=-26-34 | | -9.1y=-283.92 | | -8c+7=-9 | | 8=9w+3/2+5w+7/6 | | 5*14= | | 68+100+100= | | 6x^2+7x-13=0 | | -1/x^2=0 | | -1/x^2 | | 2(7x-4)+4x=4x-8+14x | | 9x+4=7x+7 | | 3(3x-5)+3x=4x-17+8x | | 2-b=21 | | -9x+7=-5x+19 | | 3w^2+28+9=0 | | 2t-5=3(t+4) | | y=-8x+25 | | d/2-3=10 |